#### Answer

-4

#### Work Step by Step

We are given that $g(x)=-x^{2}+4x+1$. In order to evaluate the function at x=-1, we can plug in -1 to the function and evaluate directly.
$g(-1)=-x^{2}+4x+1=-(-1)^{2}+4(-1)+1=-(1)+(-4)+1=-1-4+1=-4$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-4

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.